John P. Slough the forgotten Civil War general - Miller, Richard Lawrence 1949- (University of New Mexico Press, 2021)
"John Potts Slough, the Union commander at the Battle of Glorieta Pass, lived a life of relentless pursuit for success that entangled him in the turbulent events of mid-nineteenth-century America. As a politician, Slough fought abolitionists in the Ohio legislature and during Kansas Territory's fourth and final constitutional convention. He organized the 1st Colorado Volunteer Infantry after the Civil War broke out, eventually leading his men against Confederate forces at the pivotal engagement at Glorieta Pass. After the war, as chief justice of the New Mexico Territorial Supreme Court, he struggled to reform corrupt courts amid the territory's corrosive Reconstruction politics. Slough was known to possess a volcanic temper and an easily wounded pride. These traits not only undermined a promising career but ultimately led to his death at the hands of an aggrieved political enemy who gunned him down in a Santa Fe saloon. Recounting Slough's timeless story of rise and fall during America's most tumultuous decades, historian Richard L. Miller brings to life this extraordinary figure"--
Keywords: Slough, John Potts -- 1829-1867; Slough, John Potts / -1867; Generals / United States / Biography; Judges / New Mexico / Biography; New Mexico / Politics and government / 1848-1950; Biografie